THE PHONOLOGICAL PERSPECTIVE OF TEACHER INSTRUCTIONAL TALK IN ENGLISH CLASSROOM INTERACTION - Sirajuddin, Suharti (ELT WORLDWIDE, 2015)
Instructional[u1]Â  talk has a decisive position in teaching and learning process. The question will arise when teacher instructional talk deals with phonological perspective. Phonological here wants to figure out teachersâ pronunciation of teacher instructional talk.Â Â Â Â Â  The research aimed at finding and analyzing (i) the instructional talk that teachers use in the classroom interaction, (ii) teachersâ modification of their instructional talk in phonological perspective (iii) studentsâ perception of instructional talk used by the teachers in classroom interaction. This research applied descriptive qualitative and the total number of participants were 2 English teachers and 6 students who were divided based on their grade. The instrument used for this study was classroom observation, video recording and interview.Â Â Â Â Â  The finding indicated that (i) the first participant used 15 instructional talks and the second participant used 14 instructional talks (ii) teachers modify their talk by substitution, deletion, and addition. First participant used substitution 151 times (81%), deletion 22 times (12%), and addition 13 (7%). The second participant used substitution 30 times (83%), deletion 12 times (13%) and additional 4 (4%). (iii) Students have lower perception of teacher instructional talk which indicates students get 11 (11%) for each VII grade students and the VIII grade students get variety level percentage; 12 (21%), 15(26%) and 11 (19%) for each students. It also finds three factors that influence studentsâ perception; teachersâ factors, limited time and environment.Â Â Â Â Â Â Â Â Key words: Phonological perspective, instructional talk, classroom interactionÂ